Volatile organic compounds in beef and pork by gas chromatography‐mass spectrometry: A review. Issue 9 (14th July 2022) - Vilar, Elena Garicano; O'Sullivan, Maurice G.; Kerry, Joseph P.; Kilcawley, Kieran N.
Abstract: The aroma of meat is an integral part of flavor and therefore an essential element for consumer acceptance. Aroma compounds are challenging to extract, concentrate, separate, identify, and quantify due to the complexity of meat. A wide range of volatile compounds of different properties (molecular weight, polarity, vapor pressure) are present in raw meat at varying concentrations, and further exacerbated post cooking due to the creation of additional volatiles through mainly Maillard reactions and lipid oxidation reactions. The volatiles identified in cooked meats include hydrocarbons, alcohols, aldehydes, ketones, carboxylic acids, esters, lactones, ethers, heterocyclic constituents, and sulfur‐/halogen‐containing components. From published research, some of the key volatiles influencing cooked beef/pork flavor include hexanal, octanal, nonanal, 1‐nonanal, (E, E)‐2, 4‐decadienal, methional, 3‐methyl‐1‐butanol, methanethiol, 2‐furfurylthiol, 2‐metyl‐3‐furanthiol, 3‐mercapto‐2‐pentanone, 4‐hydroxy‐2, 5‐dimethyl‐3‐(2H)‐furanone, 1‐penten‐3‐one, 2‐pentyl‐furan, N ‐morpholinomethyl‐isopropyl=sulfide, and methyl butyrate. GC‐MS is the method of choice for their separation and identification. The technical options available have never been greater to elucidate these key volatiles impacting sensory perception. This review presents a summary of the main extraction/concentration techniques, highlighting their potential pros and cons, how advances in two‐dimensional gas chromatography may help elucidate more key aroma compounds, and outlines the benefits of olfactometry to determine the main odor‐active volatiles in beef and pork.